Experimental and computational analysis of plates under air blast loading - Jacinto, Abel Carlos (2001)
The main objective of this paper is the comparison between testing and numerical responses of metallic plates subjected to explosive loads, in order to obtain guides to the numerical modeling and analysis of this phenomenon. Moreover, the secondary objective was to provide data that could be used for checking the accuracy of a variety of calculation methods. A set of four tests at natural scale is presented on two nonstiffened metallic steel plates with different boundary conditions (one clamped in the soil and another clamped in the four edges), subjected to the action of pressure waves originated by the detonation of explosive loads. The time history of the acceleration in different points of both plates and the pressure waves in selected points, are recorded. On the other hand, a linear dynamic analysis of the plate models with the code ABAQUS was carried out. The influence of the number of natural modes that are considered for the analysis and the refinement of the mesh are analyzed. Moreover, a nonl inear geometric analysis was carried out in order to verify this possible behavior in the first plate. Suggestions to computational modeling of structures under impulsive loads arise from the comparison of numerical and experimental results. © 2001 Elsevier Science Ltd. All rights reserved.